Internal Migration: An Analysis of Associated Risks and Vulnerabilities of Women and Youth in KwaZulu-Natal - Dlamini, Nolwazi; Anwana, Emem; Reddy, Maliga (African Journal of Inter/Multidisciplinary Studies, 2024)
The abolition of the apartheid regime and the democratic process of 1994 led to the freedom of movement within South Africa. According to data, KwaZulu-Natal Province has had the second-highest rate of migration since 2000. The labour market and the provision of services are significantly impacted by these migration patterns. This paper analyses the migration patterns of women and youth in KwaZulu-Natal Province, as it examines the associated risks and vulnerabilities. The primary data for the study was obtained from the KwaZulu-Natal Department of Social Development and International Organization for Migration, unpublished report based on research it commissioned in 2014. The target population of this study comprises women and youth between the ages of 15-39 years old from all 11 districts of KwaZulu-Natal as they are more likely to migrate. Multi-stage sampling was used to select the clusters, households and ultimately the individuals to be surveyed. A cross-sectional survey of 1783 respondents were selected from various households in KwaZulu-Natal. Findings indicated that most of the women and young people who migrated did so for economic reasons. Findings also indicated that the migrants were exposed to health risks, gender-based violence, sexual exploitation, contracting and spreading the human immunodeficiency virus as well as exposure to danger to life and property. The paper contributes to a deeper understanding of migration patterns and their implications within the KwaZulu-Natal province of South Africa. The theoretical framework guiding this study is the "Push and Pull theory", which helps to elucidate the factors motivating and influencing migration decisions among young people in the region.